2009
DOI: 10.1007/s12015-009-9097-6
|View full text |Cite|
|
Sign up to set email alerts
|

Bone marrow Derived Pluripotent Cells are Pericytes which Contribute to Vascularization

Abstract: Pericytes are essential to vascularization, but the purification and characterization of pericytes remain unclear. Smooth muscle actin alpha (alpha-SMA) is one marker [corrected] of pericytes. The aim of this study is to purify the alpha-SMA positive cells from bone marrow and study the characteristics of these cells and the interaction between alpha-SMA positive cells and endothelial cells. The bone marrow stromal cells were harvested from alpha-SMA-GFP transgenic mice, and the alpha-SMA-GFP positive cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
2
45
0
1
Order By: Relevance
“…ASCs and BMSCs are similar in the expression of surface markers according to our study as well as previously published reports (7)(8)(9)29). Specifically, we found CD34, a surface marker of hematopoietic cells, negative or weakly positive, in both ASCs (8.23%) and BMSCs (10.13%), whereas CD146, a surface marker of mesenchymal stem cells, was positive in both (64.22% and 76.03%), implying a shared origin of ASCs and BMSCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ASCs and BMSCs are similar in the expression of surface markers according to our study as well as previously published reports (7)(8)(9)29). Specifically, we found CD34, a surface marker of hematopoietic cells, negative or weakly positive, in both ASCs (8.23%) and BMSCs (10.13%), whereas CD146, a surface marker of mesenchymal stem cells, was positive in both (64.22% and 76.03%), implying a shared origin of ASCs and BMSCs.…”
Section: Discussionsupporting
confidence: 92%
“…Cai et al reported that BMSCs and ASCs were both smooth muscle actin (SMA) positive pericytes (7)(8), which agrees with Yang et al 's results that ASCs were CD34 negative and SMA positive, and belonged to a subset of pericytes (9). On the other hand, Lin et al claimed ASCs were CD34 posi-tive and SMA negative and thus, were not pericytes (10).…”
Section: Introductionmentioning
confidence: 56%
“…It is consistent with our previous finding using 2D imaging that hMSCs serve as pericytes. 31 However, in comparison, the 3D imaging provides better evidence for the role of hMSCs in stabilizing the microvessels formed by HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the main expression of ADAM12 may be observed during embryonic morphogenesis of skeletal muscles and visceral organs, and intriguingly this molecule may be newly expressed in several human fibrotic diseases 21,22,23,24,25,26 . Previously, we showed that because mesenchymal progenitors, which are generally considered an alternative source of functional pericytes 27,28 , exhibit the same phenotype and ability to differentiate of mature pericytes obtained from patients with SSc, they are involved in the generation of myofibroblasts in this disease 3,4,5,14 .…”
mentioning
confidence: 99%